Linguistic Methods in Sentence Analysis - Boltakulova Gulnoza Farruxovna (Zien Journals, 2022)
The present article is devoted to an actual theme of modern linguistics – linguistic methods in sentence analysis. More attention is paid to the linguistic methods in syntactic analysis of a sentence, the basic principles of comparative study of languages at the syntactic level and linguistic methods used in the analysis of tenses. Theoretical parts of the article is proved by examples.
Keywords: method; sentence; syntactic units; subject